Indoor air quality and respiratory health implication among Malay pre-school children in Puchong and Hulu- Langat, Selangor, Malaysia - Oluchi, Onwusereaka Cynthia (2017)
Background: Indoor air quality (IAQ) refers to the nature of air that circulates throughout the space where we live. Indoor air pollutant in the environment has caused a greater impact on the health of occupants’ especially preschool age who are still growing. The increased of respiratory symptoms in children have been linked to the exposure to indoor air pollutants. Children were exposed to indoor air pollutants because they spend most of their time indoors, either in school or at home. Objective: This study aimed to determine the association between indoor air pollutants (PM2.5, PM10, VOCs, temperature, mold and relative humidity) and respiratory implications among Malay preschool children in selected areas in Selangor. Methodology: A cross sectional comparative study design was used on healthy preschools children in Puchong (n=135), as the study group and Hulu Langat (n=135) as the comparative group. Preschool children in this study were selected based on inclusion criteria such as; those who are between the age of 5 and 6 years old, healthy children, those that have been in the school for at least 6 months and Malays. The respiratory symptoms were assessed using questionnaire adapted from American Thoracic Society. Indoor air quality monitoring was conducted using the following equipment; DustTrak Aerosol monitor for particulates, PbbRAE portable VOC Monitor (pbbRAE 3000) for VOCs, Q-Trak plus Model 8554 Monitor for temperature and relative humidity, TSI VelociCalc Plus Model 8386 for air velocity; Pbi DuoSAS Super 360 and Sabroud Dextrous Agar for sampling and identification of mold. Chestgraph HI-101 spirometer for lung function test. Results: Statistical analysis shows a significant higher indoor levels of PM2.5, PM10and mold in the study area except relative humidity which was higher in comparative area (p = 0.049). Besides, indoor home exposure was also assessed, analysis showed that homes of preschool children in the study area had significantly higher VOCs, Temperature, mold, PM2.5, and PM10, except relative humidity which was significantly higher in the comparative area. There was a significant difference in FEV1/FVC% (p= 0.001) and FEV1% (p=0.008) predicted among the study and comparative group. A significant association was found between the indoor air pollutant levels of PM2.5 (χ2= 15.008, p=<0.001), PM10 (χ2= 8.816, p=0.003) and cough. Exposure to indoor PM10 (χ2= 6.842, p=0.009) and VOCs (χ2= 12.153, p=<0.001) were significantly associated with FVC%. VOCs was significantly associated with FEV1% (χ2= 14.382, p=<0.001). Mold isolated from preschools in study and comparative area include; Candida albican, Aspergillus niger, Microsporium canis, Penicillium spp. Logistics regression was used to determine the main factor that influenced the respiratory symptom and the abnormality of lung function after all confounders have been controlled. Analysis showed that the risk of FEV1% abnormality increased significantly with increased in the level of PM10 (AOR=2.1, 95% CI= 2.509-8.221), VOC (AOR= 5.3, 95% CI= 1.912-14.835) and RH (AOR=14.3, 95% CI= 1.451-14.306). Conclusion: This study found a higher exposure to indoor air pollutants which may increase the respiratory symptoms and reduced lung function among preschool children in the exposed area. It is recommended that the building of the preschools should be located in places that is less expose to outdoor sources of indoor air pollutants. Mold growth was observed more in preschools that had moisture damaged building materials. Therefore, the moisture damaged building materials need to be replaced to avoid mold growth.